2009
DOI: 10.1007/s10344-009-0313-0
|View full text |Cite
|
Sign up to set email alerts
|

White Storks, Ciconia ciconia, forage on rubbish dumps in Poland—a novel behaviour in population

Abstract: Information on the foraging of White Storks on rubbish dumps, a novel behaviour in Central European populations, is presented. Observations were first made in 1999 and to date; they have been recorded on sixteen locations in Poland. From one to 348 White Storks (median=2, N=116) were observed on rubbish dumps, and most of the records (86%) were of 1-3 birds. Birds foraging on rubbish dumps were recorded from late March to early September, but the highest numbers were seen during the summer months. Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…rodents, snakes, lizards, frogs and fish between others) and even certain amount of trash. However, landfills have become in the latter years an important source of nutrients, and for that reason an increasing percentage of the population is sedentary (Blanco 1996;Kruszyk and Ciach 2010;Massemin-Challet et al 2006;Peris 2003;Tortosa et al 2002). The food provided by landfills has a positive influence in the breeding success in this species (Tortosa et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…rodents, snakes, lizards, frogs and fish between others) and even certain amount of trash. However, landfills have become in the latter years an important source of nutrients, and for that reason an increasing percentage of the population is sedentary (Blanco 1996;Kruszyk and Ciach 2010;Massemin-Challet et al 2006;Peris 2003;Tortosa et al 2002). The food provided by landfills has a positive influence in the breeding success in this species (Tortosa et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…We observed that they also forage on exposed human food leftovers, which are not disposed in dustbins due to cultural norms prohibiting food waste (Figure A3). Trash accumulated in urban areas is known to attract other wildlife species to cities, including spotted hyenas in Ethiopia (Yirga et al, 2015), white storks in Poland (Kruszyk & Ciach, 2010), coyotes in Canada (Murray et al, 2016) and golden jackals in Israel (Borkowski, Zalewski, & Manor, 2011). In both neighborhoods, hyraxes avoided conventional shelters in well‐maintained areas where they were likely persecuted by maintenance workers or gardeners (Table A2).…”
Section: Discussionmentioning
confidence: 99%
“…Rice fields were identified as the main foraging habitat in Portugal (Gilbert, ), and this author reported that individuals travelled further to visit rice fields than the normal range of breeding season foraging trips, with distances matching the threshold of 5–10 km predicted from our model. White storks are known to feed intensively year‐round on landfills and nests near guaranteed food supply from landfills are highly desirable locations (Gilbert et al., ; Kruszyk & Ciach, ; Tortosa et al., ). Distances travelled during breeding to landfill sites often reach 15 km but can go up to 30 km (Gilbert et al., ; Tortosa et al., ), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%